CHINESE DRAGONS AND SEMIOTICS IN CHINESE ANIMATED FILMS: CHINESE DRAGONS AND SEMIOTICS IN CHINESE ANIMATED FILMS - Chen Yang; Siti Salmi Jamali; Adzira Husain (Jurnal Gendang Alam (GA), 2024)
ABSTRACT This paper aims to explore the relationship between the visualisation of Chinese dragon character design in Chinese animated films and the symbolism of traditional Chinese dragon culture. Characterisation in animated films is inextricably linked to the culture in which the character is set to fulfil the film role. In the design of animated characters, the visual image of the character can be combined with symbolism to show the culture in the design context. Incorporating culture into contemporary design is conducive to transmitting and disseminating culture and is one of the most important means of passing on cultural and intangible cultural heritage. The methodology used is interdisciplinary due to the need to use different theories in character design to deal with the merging of visual elements. Using the theory of character design, the theory of dragons, and the theory of semiotics, the relationship between culture and visuals in character design is matched by whether there is a deviation or a coincidence between the representation of symbols, symbolic and metaphorical meanings in Peirce’s theory of semiotics. The result is a unity between the three referential elements. It is interesting to note that different characters have different characteristics. Still, some patterns can be followed under a specific cultural background theory system, and there is consistency in the visual representation of the symbols and the cultural symbolism. Keywords: Chinese Dragon, Cultural Heritage, Chinese Animated Films, Character Design